DINAMIKA KEHIDUPAN KAUM AGAMAWAN ANALISIS WACANA KRITIS NOVEL LA FAUTE DE L’ABB É MOURET KARYA ÉMILE ZOLA - Hanafiah Azmi dan Teguh Basuki (Universitas Gadjah Mada, 2015)
During the Second Empire, the development of educational field commenced the development inother fields, such as economics and politics. These could not be separated from the influence of theChurch which at that time had a close relationship with the State. The emergence of a new social class,Bourgeoisie, had changed the life style of the society which initially oriented from the Lord to secular.They wanted a freedom of life from the control of the Church. The dominant role of the Church at first,it gradually shifted along with increasing role of the new social class. This research discussed about thelife of the society during the Second Empire, represented by Émile Zola on the novel La Faute de l’AbbéMouret through the life of the clergyman. The problems which arised from himself (internal) and of thesurroundings (external), pushed the main character to leave his life in the Church and took off his statusas a clergyman.